Stress and Obesity. [article]. - Tomiyama, Janet A.
Many pathways connect stress and obesity, two highly prevalent problems facing society today. First, stress interferes with cognitive processes such as executive function and self-regulation. Second, stress can affect behavior by inducing overeating and consumption of foods that are high in calories, fat, or sugar; by decreasing physical activity; and by shortening sleep. Third, stress triggers physiological changes in the hypothalamic-pituitary-adrenal axis, reward processing in the brain, and possibly the gut microbiome. Finally, stress can stimulate production of biochemical hormones and peptides such as leptin, ghrelin, and neuropeptide Y. Obesity itself can be a stressful state due to the high prevalence of weight stigma. This article therefore traces the contribution of weight stigma to stress and obesogenic processes, ultimately describing a vicious cycle of stress to obesity to stigma to stress. Current obesity prevention efforts focus solely on eating and exercise; the evidence reviewed in this article points to stress as an important but currently overlooked public policy target. -- (from the author)